MENJADIKAN MATA KULIAH PENDIDIKAN PANCASILA SEBAGAI MEDIA PENANAMAN NILAI-NILAI BELA NEGARA - Anggita Sari, Wiwin; Lian, Bukman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
National defense is not only to maintain the unity of the Republic of Indonesia, but it must be realized in real life to create critical, loyality, and determination of the nation. This study aimed at finding out the efforts to build the value of defending nation through the Education of Pancasila in Universitas PGRI Palembang. The method used was qualitative case study. The techniques used for collecting data were interview, documentation, observation and literature review. The data collection, data reduction, data presentation, and conclusions were analyzed simultaneously and interactively by using qualitative analysis. The result of this research stated that (1) the students of Universitas PGRI Palembang still had limited knowledge about the values of nation defense, (2) the students did not have critical attitude towards the problems around them, (3) the students had low achievement in motivation. The efforts done by Universitas PGRI Palembang in handling with these problems were fostering: (1) the values of love of the nation (2) fostering the value of national and state awareness, (3) fostering the values of Pancasila as the ideology of the nation, 4) the value of loyalty to the nation, (5) the knowledge of nation defense, and (6) the spirit of achievement as a reflection of the love of the nation.